The Influence of Knowledge of Partai Keadilan Sejahtera (PKS) Cadres on the Preference of Saving in Sharia Bank with Religiosity as a Moderating Variable - Ahmad Ripai Saragih; Nurlaila Nurlaila; Tuti Anggraini (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this research is to determine the effect of knowledge on saving preferences in Sharia banks and to determine the role of religiosity in moderating knowledge of saving preferences in Sharia banks. The approach is quantitative research. The research subjects were Partai Keadilan Sejahtera (PKS) Cadres in Percut Sei Tuan District. The results of this study indicate that the results of multiple linear regression analysis with the use of Moderated Regression Analysis (MRA) partially indicate that the knowledge variable (X1) has a positive and significant effect on saving preferences in Sharia bank, while the moderating variable, namely religiosity (Z) has an effect positive and significant towards saving preferences (Y) in Sharia banks. The variable multiplication between the independent variable and the moderating variable is PR (Knowledge x Religiosity) where the religiosity variable moderates by weakening the relationship between the knowledge variable and the preference variable for saving in Sharia banks. Religion is not able to moderate the effect of knowledge on saving preferences in Sharia banks. The results of multiple linear regression analysis with the simultaneous use of Moderated Regression Analysis (MRA) show that simultaneously influencing the dependent variable, namely the preference for saving in Sharia bank with a significant level of 0.000 <0.05 and calculated F value =1748,102 and F table =3,939, so 1748.102>3,939. Factor variations based on the results of multiple linear regression analysis with the use of Moderated Regression Analysis (MRA) that each variable is able to explain, variation of Preferences for Saving in Sharia bank of 98.1%. Meanwhile, another 1.9% is influenced by other variables outside the model.